Strategi Penguatan Potensi Lokal UMKM Batik Tulis Goluak Loge Untuk Mendukung Pembangunan Di Desa Logas Kabupaten Kuantan Singingi - Hilmah Zuryani; Rahmita Budiartiningsih; Cut Endang Kurniasih; Zulfadil Zulfadil; Fakhri Rabialdy (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze strategies for strengthening the local potential of Goluak Loge Batik Tulis MSMEs to support development in Logas Village, Kuantan Singingi Regency. Data was collected through questionnaires and interviews with respondents, namely the Logas Village government, Goluak Loge Written Batik MSME Workers and village residents who had bought the batik. The analysis uses SWOT and qualitative descriptive. The research results show that based on the SWOT analysis diagram image, this strategy is in quadrant 2 (OW). The strategy used is to change the old strategy into a new strategy, because stability in quadrant 2 indicates that this MSME is weak but has great opportunities. If you change your strategy, these MSMEs have the potential to continue to grow.